2019
DOI: 10.1055/s-0039-1677793
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Superficial Vein Thrombosis: A Systematic Review and Meta-Analysis

Abstract: Background The optimal first line treatment for patients with isolated superficial venous thrombosis (SVT) of the lower extremity is unknown. Objective This article reports estimates of the rate of venous thromboembolic complications among patients with SVT according to treatment. Materials and Methods A systematic review and meta-analysis was performed using unrestricted searches of electronic databases. Reported events were transformed to event per 100 patient-years of follow-up and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 35 publications
0
39
0
3
Order By: Relevance
“…A recent systematic review and meta-analysis showed that fondaparinux achieved the lowest rate of DVT or PE (1.4 events per 100 patient years of follow up), and that for other treatments there was low quality evidence preventing firm conclusions about the optimal treatment for SVT. 272 In SURPRISE, an open label, non-inferiority phase IIIb RCT, 472 patients with symptomatic SVT were randomised to receive 10 mg oral rivaroxaban or 2.5 mg subcutaneous fondaparinux o.d. for 45 days.…”
Section: Diagnosis and Workupmentioning
confidence: 99%
“…A recent systematic review and meta-analysis showed that fondaparinux achieved the lowest rate of DVT or PE (1.4 events per 100 patient years of follow up), and that for other treatments there was low quality evidence preventing firm conclusions about the optimal treatment for SVT. 272 In SURPRISE, an open label, non-inferiority phase IIIb RCT, 472 patients with symptomatic SVT were randomised to receive 10 mg oral rivaroxaban or 2.5 mg subcutaneous fondaparinux o.d. for 45 days.…”
Section: Diagnosis and Workupmentioning
confidence: 99%
“…Similarly, there are no clear guidelines to the nonetheless common clinical scenario of isolated superficial venous thrombosis. The systematic review and meta-analysis investigating therapeutic alternatives from Duffet et al 35 was thus very welcome, as reflected by the high Altmetrics Attention score it obtained. Also, very well received were the efforts from the Japan Environment & Children's Study Group who took advantage of a large Japanese cohort of more than 100,000 pregnancies to assess risks factors for VTE in pregnancy and post-partum.…”
Section: Addressing Less Commonly Studied Situationsmentioning
confidence: 95%
“…established that anticoagulant therapy with Fondaparinux is more effective than placebo, Rivaroxaban is non-inferior to Fondaparinux, (4)(5)(6) and that SVT is closely linked to deep vein thrombosis (DVT) and pulmonary embolism (PE), thus highlighting the potential severity of the disease. (7-10) A number of observational studies published in the last years reveal that one in every four patients presenting with SVT in the lower limbs may also have DVT or PE concomitantly.…”
Section: Accepted Manuscriptmentioning
confidence: 99%